Atom Column Indexing: Atomic Resolution Image Analysis Through a Matrix Representation. (17th November 2014) - Sang, Xiahan; Oni, Adedapo A.; LeBeau, James M.
Abstract Here, we report the development of an approach to map atomic resolution images into a convenient matrix representation. Through the combination of two-dimensional Gaussian fitting and the projective standard deviation, atom column locations are projected onto two noncollinear reference lattice vectors that are used to assign each a unique (i, j) matrix index. By doing so, straightforward atomic resolution image analysis becomes possible. Using practical examples, we demonstrate that the matrix representation greatly simplifies categorizing atom columns to different sublattices. This enables a myriad of direct analyses, such as mapping atom column properties and correlating long-range atom column pairs. MATLAB source code can be downloaded from https://github.com/subangstrom/aci.